Exploring linguistic phenomena in technical translation discourse - (:unkn) unknown (Peter Lang AG, 2018)
When describing what technical translation is and what is not, the examination of the theoretical frameworks within which technical translation operates is of the utmost importance. Technical translators with a relevant degree are assumed to have been equipped with the theoretical and conceptual tools which are thought to enable them to effectively deal with previously unencountered situations as they emerge in professional workplace. Yet, with various intended learning outcomes and objectives in the curriculum, it is hardly any doubt that the academic training programs are naturally designed only to familiarize the future translators with the texts that are typically translated in scientific and technical domains. Likewise, given the enormous diversity of scientific and technical expressions today, scientific and technical terminology is too vast and complex to be fully mastered. Technical discourse being unique, the kinds of competences that may be expected of technical translators are not anything like those to be expected from translators of literary texts. It is not wrong to assume that general translation strategies may not embrace the reality of translation as a form of technical communication, which suggests that without the background knowledge of technical communication being incorporated into the theory and practice of translation in general, technical translators will require a variety of other tools to understand the processes necessary to create a target text involving technical information. This study aims at revealing how linguistic phenomena which have fed into the developments in translation theory can bring new insight to the technical translator’s task. Technical translators produce texts and crafting a new text requires the ability to observe the norms of textuality and to be sensitive to the genre conventions of the target culture. Thus, in dealing with terminology in different kinds of specialized texts, technical translators will need the tools and concepts that come from linguistics and other related (sub) fields, such as textlinguistics, pragmatics, and semiotics. © Peter Lang GmbH.